COMPARATIVE ANALYSIS OF DAMD, ISSR AND SCOT MOLECULAR MARKERS ON CRYOPRESERVED LUDISIA DISCOLOR AXILLARY BUDS: DAMD, ISSR AND SCOT MOLECULAR MARKERS ON CRYOPRESERVED LUDISIA DISCOLOR - Subramaniam, Sreeramanan; Selva Rajan, Kirutika; Burkhan, Hazirah; Chew, Bee Lynn; Appalasamy, Suganthi; Poobathy, Ranjetta (Malaysian Journal of Science, 2022)
Ludisia discolor, a jewel orchid is the only species found under its genus (Ludisia). This wild orchid is well known for its striking foliage and its medicinal benefits. Since the population of this valuable species is becoming scarce, therefore protecting this orchid is crucial. Cryopreservation is a practicable long-term germplasm conservation approach. The genetic material is stored at freezing temperature using liquid nitrogen. In this study, V cryo-plate method was developed using L. discolor axillary buds using optimum conditions. For the screening of somaclonal variation, 3 weeks old treated (cryopreserved and non-cryopreserved) explants were utilized in comparison with the stock cultures as a control. The genetic stability was assessed using a total of twenty (20) DAMD, twenty (20) ISSR, and ten (10) SCoT molecular markers. The somaclonal variation detected in cryopreserved explant using DAMD, ISSR, and SCoT molecular markers were 12.5, 4.17, and 10.53% respectively. However, somaclonal variation was also detected in non-cryopreserved explants using DAMD, ISSR, and SCoT at 6.15, 5.77, and 10%, respectively. Hence, SCoT was chosen to be precise than the other two molecular markers (DAMD and ISSR).